Genetic diversity analysis of Mecheri sheep using microsatellite markers - R Selvam; PS Rahumathulla; S N Sivaselvam; SMK Karthickeyan; R Rajendran (Journal of Livestock Biodiversity, 2025)
Genetic characterization of native breeds is the most significant step in safeguarding our germplasm. The present study aims to characterize Mecheri, a sheep mutton breed of Tamil Nadu, India based on microsatellite polymorphism. The animals of the breed are medium sized with compact body and covered with short hairs, which are usually not shorn. The animals are light brown in colour. Both males and females are polled and the breed occupies first position in terms of population and area of distribution in the state. Microsatellites are the markers of choice for genetic diversity analysis. The genomic DNA from 50 unrelated Mecheri sheep were PCR-amplified with a panel of 10 microsatellite markers and resolved through 6 per cent denaturing polyacrylamide gel electrophoresis followed by silver staining. The number of alleles ranged from 4 to 15 with allele sizes ranging from 96 to 154 bp. The allele frequencies ranged from 0.011 to 0.484. Polymorphism information content (PIC) ranged from 0.798 to 0.878. The population was deviating from Hardy-Weinberg equilibrium at most of the investigated loci, except two. The observed and expected heterozygosities ranged from 0.927 to 1.000 and 0.583 to 0.878. The set of microsatellite loci used in this study exhibited high genetic polymorphism and thus represented a useful panel of markers for population genetic studies in Indian sheep breeds.